2012
DOI: 10.1016/j.biomaterials.2011.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Cationic glycopolymers for the delivery of pDNA to human dermal fibroblasts and rat mesenchymal stem cells

Abstract: Progenitor and pluripotent cell types offer promise as regenerative therapies but transfecting these sensitive cells has proven difficult. Herein, a series of linear trehalose-oligoethyleneamine “click” copolymers were synthesized and examined for their ability to deliver plasmid DNA (pDNA) to two progenitor cell types, human dermal fibroblasts (HDFn) and rat mesenchymal stem cells (RMSC). Seven polymer vehicle analogs were synthesized in which three parameters were systematically varied: the number of seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 45 publications
4
46
0
Order By: Relevance
“…31, 32, 34 The ring-opening polymerization of VB-Glu-NCA with PEG-amine as the macroinitiator yielded PEG- block -poly(γ-(4-vinylbenzyl)-L-glutamate) (PEG- b -PVBLG) with controlled molecular weights (MWs) and narrow molecular-weight distributions (Scheme 2). At the VB-Glu-NCA/PEG-amine ratio of 100, the obtained M n of 20.7 × 10 3 g·mol -1 agreed well with the theoretical M n of 24.6 × 10 3 g·mol -1 and had a narrow molecular weight distribution of 1.21 (entry 1, Table 1). Two PEG- b -PVBLG copolymers were prepared with degrees of polymerization (DP) of 76 (PEG- b -PVBLG 76 ) and 287 (PEG- b -PVBLG 287 ) of the PVBLG block (Table 1).…”
Section: Resultssupporting
confidence: 75%
“…31, 32, 34 The ring-opening polymerization of VB-Glu-NCA with PEG-amine as the macroinitiator yielded PEG- block -poly(γ-(4-vinylbenzyl)-L-glutamate) (PEG- b -PVBLG) with controlled molecular weights (MWs) and narrow molecular-weight distributions (Scheme 2). At the VB-Glu-NCA/PEG-amine ratio of 100, the obtained M n of 20.7 × 10 3 g·mol -1 agreed well with the theoretical M n of 24.6 × 10 3 g·mol -1 and had a narrow molecular weight distribution of 1.21 (entry 1, Table 1). Two PEG- b -PVBLG copolymers were prepared with degrees of polymerization (DP) of 76 (PEG- b -PVBLG 76 ) and 287 (PEG- b -PVBLG 287 ) of the PVBLG block (Table 1).…”
Section: Resultssupporting
confidence: 75%
“…45 Additionally, it would seem that the carbohydrate residues in G4 allow it to transfect primary and mesenchymal stem cells to a greater extent than JetPEI™. 46 Taken together, the data from these prior experiments as well as the current data illustrate how slight changes in polymer structure (in this case, the number of hydroxyl groups per repeat unit) can impact their pDNA delivery mechanisms.…”
Section: Discussionsupporting
confidence: 59%
“…it may induce antinociception in vivo. 23 However, we have demonstrated that triptolide alone does not modify MKP-1, MKP-3, or MAPKs in lipopolysaccharide-stimulated microglial cells. 31 Moreover, our laboratory and others have shown that triptolide effectively blocks MKP-1 and MKP-3 when the expression of these MKPs is enhanced, and consequently blocks pharmacological anti-inflammatory effects in vitro.…”
Section: Methodsmentioning
confidence: 65%